Risco de morbidade no primeiro ano de vida em filhos de mães adolescentes de baixa renda - Parahyba, Marilia Joffily Pereira da Costa (2002)
Introduction: The immediate repercussions of a teenage motherhood, both on the women and their children, are widely addressed in the literature. However, it is not clear which are the medium and long-term effects the teenage and low income status of the mothers have on their offspring. The first year of life, the most vulnerable period in life to aggressions of any kind, seems to be the most critical stage for the effects of such conditions to appear. Objective: Verify which factors or conditions could determine a higher morbidity risk in children under one year of age. Methodology: Transversal-type study, carried out between March 2001 and March 2002 at the Integrated Medical Care Center (Núcleo de Atenção Médica Integrada), Fortaleza University, and at the Albert Sabin Hospital for Children (Hospital Infantil Albert Sabin - HIAS). The study variables contemplate the mothers and children approaching behaviors, social, economics, demographic and biological aspects. Results: 296 mothers were studied, with ages ranging between 14-19 years, and their not older than one year children, all of them registered at the above mentioned healthcare services. The mothers’ average school-attending time was 6,5 years, and 8,1% of them performed a remunerated activity. There was no significant association between child disease and the mother’s literacy level (p>0,05). The family’s income was one minimum wage in 75,5% of the cases. An important number of mothers (65,2%) would have preferred to wait longer before getting pregnant, and 19,5% of them tried an abortion. There was no significant association between child disease and these variables. Of the mothers under 16, 17,7% newborn weight were equal or less than 2500g, as from the more than 16, 13,0% newborn weight was the same (p>0,05). Separately, youngest mothers procreated newborn weight lower than oldest mothers (p<0,05). Almost 60,0% of the women do take care of their children. The oldest take care more than the youngest (p<0,05) and 11 the single less than the married (p<0,05). Women that accept financial help take care more than that ones who do not accept (p<0,05). There was no significant association between child care and disease (p>0,05). The average age of the children was 3,5 months, and 99,2% of them had Child Card (Cartão da Criança). It was good the vaccination status. The average breast-feeding period was 117 days for exclusive breast-feeding, and 180 days for a mixed feeding. A statistically significant association was found between the breast-feeding period and the occurrence of child diseases (p<0,05). The most common pathologies were the IRAs (44,8%), skin affections (21,1%), and diarrhea (18,2%). The incidence of child morbidity was not influenced by the desire, or lack of desire, of the mother to get pregnant (p>0,05). The gestational age at birth, the newborn’s vitality and birth weight did not show to be significant parameters affecting child morbidity. Conclusion: The main factor for children’s sickness was the short period of breast-feeding. Recommendation: The results of the study suggests that teenage mothers should be oriented about how to manage child diseases, and be given information regarding the normal growth and development of their children as well to prevent new pregnancy